Surgeon – Therapist Communication: Do All Members See Eye-to-Eye?. Issue 4 (2nd October 2015) - Longstaffe, Robert; Slade Shantz, Jesse; Leiter, Jeff; Peeler, Jason
Abstract: Background. Poor interprofessional collaboration has been shown to negatively affect patient care within many fields of medicine. Growing evidence is suggesting that improved interprofessional collaboration can positively affect patient care. Postoperative rehabilitation of many orthopedic conditions necessitates the combined efforts of surgeons, and therapists. There is a paucity of literature examining collaboration among orthopedic surgeons and therapists regarding postoperative rehabilitation. Objectives. The following study examines the perceived quality of communications between orthopedic surgeons and therapists employing an online survey. We hypothesized that collaborative practice patterns result in improved perceptions of communication. Methods. Ethics board approval was obtained. Subjects consisted of orthopedic surgeons, licensed physiotherapists and certified athletic therapists. The online survey was distributed through the Canadian Orthopaedic Association (COA), the Canadian Physiotherapy Association (CPA) and the Canadian Athletic Therapists Association (CATA). Data analysis was performed using Stata/IC 12.1 (Stata Corp, College Station, TX, USA). Descriptive statistics were calculated to determine the median responses and ranges. Median responses were compared using the Kruskal–Wallis one-way analysis of variance. Qualitative analysis regarding text responses was performed by three reviewers. Results. Reponses were received from all specialties (COA 164, CPA 524, CATA 163). There were significant differences in the perceived quality of communication by quantitative and qualitative analysis ( p < 0.001). Analysis of communication within practice patterns of stand-alone versus collaborative revealed improved perception of communication quality with increased contact. 65.6% of responders that practiced as stand-alone had a negative view of interprofessional communication. 48.4% of responders in a collaborative practice had a positive view of interprofessional communication. Analysis of the preferred form of communication found that orthopedic surgeons felt the most useful referral information was a pre-printed consult sheet (odds ratio [OR] = 1.56, p < 0.001), whereas therapists were more likely to rank consult notes (OR = 1.27, p < 0.042) and operative reports (OR = 1.20, p < 0.092) as a more useful form of communication. Conclusions. Collaborative practice shows improved perceptions of communication between specialties. Orthopedic surgeons perceive a higher quality of communication than therapists. Therapists and orthopedic surgeons also do not agree on the information that should be relayed between the specialties regarding postoperative rehabilitation.